2020
DOI: 10.1152/ajpgi.00286.2019
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D signaling maintains intestinal innate immunity and gut microbiota: potential intervention for metabolic syndrome and NAFLD

Abstract: A lack of sunlight exposure, residence in the northern latitudes, and dietary vitamin D insufficiency are coprevalent with metabolic syndrome (MetS), Type 2 diabetes (T2D), and nonalcoholic fatty liver diseases (NAFLD), implying a potential causality and underlying mechanism. Whether vitamin D supplementation or treatment can improve these disorders is controversial, in part, because of the absence of large-scale trials. Experimental investigations, on the other hand, have uncovered novel biological functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…The physiological functions of VDBP are diverse. Specifically, VDBP is the primary plasma transporter for VD and its metabolites, and may promote Mets, type-2 diabetes, and NAFLD occurrence by affecting plasma levels of VD [46]; VDBP is a transport of fatty acids and may be related with lipid metabolism [47]; VDBP plays a role in inflammatory process by activating macrophage and C5a-mediated chemotaxis [48]. All the functions suggested that VDBP may have the potential effects on the pathogenesis of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological functions of VDBP are diverse. Specifically, VDBP is the primary plasma transporter for VD and its metabolites, and may promote Mets, type-2 diabetes, and NAFLD occurrence by affecting plasma levels of VD [46]; VDBP is a transport of fatty acids and may be related with lipid metabolism [47]; VDBP plays a role in inflammatory process by activating macrophage and C5a-mediated chemotaxis [48]. All the functions suggested that VDBP may have the potential effects on the pathogenesis of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…One area of intense interest in the field is the association between altered gut microbiota and their metabolites and NAFLD [47]. Indeed, vitamin D status may influence the severity of NAFLD through its effects on intestinal innate immunity and gut microbial composition [48]. There is also some indirect support for a potential role of vitamin D-regulated AMPs in attenuating NAFLD.…”
Section: Regulation Of Amp Responses By Calcitriol Signaling In Human...mentioning
confidence: 99%
“…Such processes are important for intracellular bacteria killing [ 43 ]. Evidence from animal studies demonstrates that lacking vitamin D impairs gut innate immunity, leading to gut dysbiosis and systemic inflammation [ 44 ]. In addition, vitamin D 3 improves protective effects of other cells participating in the innate immune system as first-barrier defenses, such as keratinocytes, epithelial, intestinal, lung and corneal cells, and placenta trophoblasts [ 45 ].…”
Section: Immunomodulatory Potential Of Vitamin Dmentioning
confidence: 99%